Remote sensing of drought innovative monitoring approaches - Wardlow, Brian D.; Anderson, Martha C.; Verdin, James P. (CRC Press, 2012)
"Since the late 1990s, remote sensing capabilities for operational drought monitoring have greatly expanded. This book presents remote sensing-based approaches that are currently used or could be used for large-area drought monitoring. The text covers applications for vegetation condition monitoring, soil moisture and ET estimation, and precipitation estimation. Each chapter includes a literature review, a technical description of the remote sensing instrument or data and the methodology used, examples and discussion of the products and information that are derived and how they can be applied to drought monitoring, and discussion of future work and considerations for using the technique"-- Provided by publisher.
Keywords: Droughts -- Remote sensing.; elektronické knihy; electronic books